2005
DOI: 10.1080/07853890510007304
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerosis and innate immune signaling

Abstract: Atherosclerosis, the leading cause of death in developed countries, is characterized by chronic inflammation in the artery wall. It has been appreciated for decades that this disease is linked to hypercholesterolemia and the accumulation of macrophages in the artery wall, yet the exact mechanisms underlying this inflammatory process remain unclear. The role of innate and adaptive immune responses in the pathogenesis of atherosclerosis has been an area of intense study. It now appears that activation of innate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 56 publications
0
17
0
2
Order By: Relevance
“…1 In addition, the inappropriate activation of these receptors by endogenous self ligands can contribute to chronic inflammatory syndromes and autoimmunity. [2][3][4] Several families of PRRs have been described, including the Toll-like receptors (TLRs), C-type-lectins, NOD-like receptors (NLRs), and RNA helicases. 1,[5][6][7] Another class of PRRs are the scavenger receptor (SRs) family of proteins (Fig.…”
mentioning
confidence: 99%
“…1 In addition, the inappropriate activation of these receptors by endogenous self ligands can contribute to chronic inflammatory syndromes and autoimmunity. [2][3][4] Several families of PRRs have been described, including the Toll-like receptors (TLRs), C-type-lectins, NOD-like receptors (NLRs), and RNA helicases. 1,[5][6][7] Another class of PRRs are the scavenger receptor (SRs) family of proteins (Fig.…”
mentioning
confidence: 99%
“…Antioxidants are reduced during disease states common to ICU patients such as COPD, acute lung injury, atherosclerosis, and acute renal failure [43,56,57]. These antioxidants are produced by skeletal muscles [53].…”
mentioning
confidence: 99%
“…Experimental models using these organisms, such as P. gingivalis (39), show that they can indeed induce atherosclerotic inflammation, although the mechanism(s) by which they might promote this disease is not clear. It has been proposed recently that innate recognition by TLR2 in conjunction with either TLR1 or TLR6 of a wide range of microbial agonists is a potential inflammatory pathway whereby microbial moieties might be involved (17,40). In fact, Mullick et al (19) recently demonstrated that the systemic administration of the synthetic TLR2-using Pam 3 CSK 4 lipopeptide could greatly enhance atherosclerosis in a mouse model using the LDL receptor KO Ϫ/Ϫ mouse, and that disease was ablated when TLR2 was eliminated through use of Ldl Ϫ/Ϫ , TLR2 Ϫ/Ϫ mice.…”
Section: Discussionmentioning
confidence: 99%